Multiphase composite material, preparation method thereof and application of multiphase composite material in electrolyzed water

By growing a multiphase composite of NiMoO4, Mo3Se4 and Ni3Se2 on a foam nickel substrate, the problem of high overpotential in the hydrogen evolution reaction under alkaline conditions is solved, and efficient and stable hydrogen production by electrolyzing water is achieved, reducing production costs.

CN119593008APending Publication Date: 2025-03-11NINGXIA MEDICAL UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411932958.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art has a high overpotential in hydrogen evolution reaction (HER) under alkaline conditions, and it is necessary to add precious metal catalysts, which are costly and inefficient.

Method used

A multiphase composite material, including foam nickel as the substrate, grow NiMoO4, Mo3Se4 and Ni3Se2 above, is prepared by hydrothermal method to form a self-supporting electrode with good conductivity.

Benefits of technology

It significantly reduces the overpotential of the HER process and improves the efficiency of hydrogen production by electrolyzing water. The material exhibits long-term stability at high current density, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593008A_ABST
    Figure CN119593008A_ABST
Patent Text Reader

Abstract

The invention relates to a multiphase composite material, a preparation method thereof and application of the multiphase composite material in electrolyzed water. The multi-phase composite material comprises foamed nickel, and NiMoO4, Mo3Se4 and Ni3Se2 which are grown on the foamed nickel. In an alkaline medium, the composite material has excellent catalytic activity on HER, the overpotential in the HER process can be remarkably reduced, the water electrolysis hydrogen production efficiency is improved, meanwhile, the multi-phase composite material shows long-term stability under high current density, and industrial application is expected to be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrocatalyst technology, and in particular to a multiphase composite material, a preparation method thereof, and an application thereof in water electrolysis. Background Art

[0002] The scarcity of fossil fuels and the environmental pollution they cause have triggered an urgent exploration of new renewable energy sources. As an ideal energy carrier, hydrogen has significant advantages in energy density and zero carbon emissions. At present, the electrolysis of water to produce hydrogen has a good development prospect. In actual industrial applications, the hydrogen evolution reaction (HER) under alkaline conditions is more favored, but this process has a high overpotential and requires the addition of suitable catalysts to reduce energy consumption. At present, the research and development hotspot of catalysts is low-cost, high-efficiency non-precious metal catalysts. When designing alkaline HER catalysts, it is an effective and feasible strategy to take into account both favorable hydrogen adsorption / desorption capabilities and accelerated water dissociation rate.

[0003] Transition metal selenides (TMSe) have attracted widespread attention due to their tunable electronic structure, narrow band gap, diverse morphology and economic performance. The HER under alkaline conditions involves three processes: (1) water adsorption, (2) water molecules gaining electrons and dissociating to generate OH - (released into the solution) and H atoms, (3) H combines with H to generate H2 and desorbs from the catalyst surface. TMSe is weakly bound to H, which is conducive to the desorption of hydrogen and can improve the alkaline HER activity.

[0004] Therefore, it is necessary to develop new hydrogen evolution reaction electrocatalysts based on TMSe. Summary of the invention

[0005] The first aspect of the present application aims to provide a multiphase composite material. The second aspect of the present application aims to provide a method for preparing a multiphase composite material. The third aspect of the present application aims to provide a use of a multiphase composite material as an electrocatalyst for hydrogen evolution reaction.

[0006] To achieve the above objectives, the present application provides a multiphase composite material in a first aspect, comprising: Nickel foam, and NiMoO4, Mo3Se4 and Ni3Se2 grown on the nickel foam.

[0007] In some embodiments, the NiMoO4 is displayed as a flower-like structure assembled from micro-sheets, and the Mo3Se4 and Ni3Se2 form a heterojunction and are displayed as a nanoparticle structure.

[0008] Herein, the term "microsheet" refers to a sheet-like structure having a thickness between 1 micrometer and 10 micrometers, for example, a sheet-like structure having a thickness of about 2 micrometers.

[0009] As used herein, the term "nanoparticle" refers to a granular or spherical structure having at least one dimension between 1 nanometer and 1000 nanometers, such as between about 400-600 nanometers, and may have a regular or irregular shape.

[0010] In some embodiments, the composite is obtained by reacting nickel foam as a nickel source with a molybdenum source and a selenium source soluble in water, wherein the molar ratio of the molybdenum source to the selenium source is 1:(3-5), preferably 1:4.

[0011] In the present application, the nickel foam has a dual role: first, it participates in the hydrothermal reaction as a nickel source to generate a complex containing NiMoO4, Mo3Se4 and Ni3Se2; second, it serves as a substrate to support the complex. Therefore, in some embodiments, the amount of nickel foam used is significantly excessive relative to the molybdenum source and selenium source participating in the reaction.

[0012] In the present application, there is no particular requirement for the types of the molybdenum source and the selenium source, as long as they can be dissolved in water and undergo a hydrothermal reaction. In some embodiments, the molybdenum source is sodium molybdate and the selenium source is selenium dioxide.

[0013] The second aspect of the present application provides a method for preparing a multiphase composite material, comprising: (1) dissolving a molybdenum source and a selenium source in water at a molar ratio of 1:(3-5) to obtain a molybdenum-selenium solution; (2) The molybdenum-selenium solution and nickel foam are subjected to a hydrothermal reaction to obtain the multiphase composite material.

[0014] The inventor unexpectedly discovered during the implementation of the technical solution of the present application that the molar ratio of the molybdenum source and the selenium source has a significant impact on the composition of the multiphase composite material. As described later, when the amount of SeO2 is small, for example, when the molar ratio of the molybdenum source to the selenium source is 1:1, the expected multiphase material cannot be formed. Only when the amount of the selenium source is significantly greater than the amount of the molybdenum source, for example, when the molar ratio of the molybdenum source to the selenium source is greater than or equal to 1:3, can the expected multiphase material be formed, that is, NiMoO4, Mo3Se4 and Ni3Se2 are formed on the nickel foam.

[0015] In some embodiments, the molar ratio of the molybdenum source to the selenium source is 1:4.

[0016] In some embodiments, the molybdenum source is sodium molybdate, and the selenium source is selenium dioxide.

[0017] In some embodiments, the reaction temperature of the hydrothermal reaction is 160-200° C., and the reaction time is 10-14 hours.

[0018] The third aspect of the present application also provides use of the multiphase composite material of the first aspect as an electrocatalyst for hydrogen evolution reaction.

[0019] As used herein, the term "hydrogen evolution reaction" refers to a reaction in which hydrogen is produced on the cathode side during water electrolysis.

[0020] Beneficial Effects The multiphase composite material provided in the present application is based on nickel foam, on which NiMoO4, Mo3Se4 and Ni3Se2 are generated in situ. The composite material uses nickel foam with good conductivity as a substrate and nickel source, and can be used as a self-supporting electrode, avoiding the use of electrode adhesives and external nickel sources, enhancing the conductivity of the material while reducing production costs; the material grown in situ on the nickel foam substrate is not easy to fall off during the electrocatalytic hydrogen evolution process as an electrocatalyst, and is efficient and stable. In alkaline media, the composite material has excellent catalytic activity for HER, can significantly reduce the overpotential of the HER process, and improve the efficiency of hydrogen production by electrolysis of water. At the same time, the multiphase composite material shows long-term stability at high current density, and is expected to be industrially applied.

[0021] In addition, the present application prepares the multiphase composite material by a one-step hydrothermal method, which is simple to operate and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The XRD patterns of samples NiMoO4 / NF (Comparative Example 1), NiMoO4 / Ni3Se2 / NF (Example 2), NiMoO4 / Mo3Se4 / Ni3Se2 / NF-3 (Example 3), NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4 (Example 1), and NiMoO4 / Mo3Se4 / Ni3Se2 / NF-5 (Example 4) prepared in Examples 1-4 and Comparative Example 1 are shown. Among them, Figure (A) shows characteristic peaks in the range of about 5-80° at 2θ angle, and Figure (B) shows characteristic peaks in the range of about 10-30° at 2θ angle in an enlarged manner.

[0023] Figure 2 These are SEM photos of the samples prepared in Examples 1-4 and Comparative Example 1, wherein a1-a4 are photos of NiMoO4 / NF, b1-b4 are photos of NiMoO4 / Ni3Se2 / NF, c1-c4 are photos of NiMoO4 / Mo3Se4 / Ni3Se2 / NF-3, d1-d4 are photos of NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4, and e1-e4 are photos of NiMoO4 / Mo3Se4 / Ni3Se2 / NF-5, wherein (c3), (d3) and (e3) are enlarged views of the red dotted boxes in (c2), (d2) and (e2), respectively, and (c4), (d4) and (e4) are enlarged views of the green dotted boxes in (c2), (d2) and (e2), respectively.

[0024] Figure 3 These are the EDS test results of NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4, where (a) is the SEM photo, (b), (c), (d), and (e) are the EDS element distribution diagrams of Ni, Mo, Se, and O, respectively.

[0025] Figure 4 The XPS results of NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4, where (a) is the Ni 2p spectrum, (b) is the Mo 3d spectrum, (c) is the Se 3d spectrum, and (d) is the O 1s spectrum.

[0026] Figure 5 The catalytic performances of samples NiMoO4 / NF (Comparative Example 1), NiMoO4 / Ni3Se2 / NF (Example 2), NiMoO4 / Mo3Se4 / Ni3Se2 / NF-3 (Example 3), NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4 (Example 1), and NiMoO4 / Mo3Se4 / Ni3Se2 / NF-5 (Example 4) are shown, where (a) is the LSV diagram (90% iR drop compensation), and (b) is the overpotential comparison (current density is 10 mA cm -2 ), (c) Tafel slope, (d) linear fitting diagram of current density change and scan rate, (e) Nyquist impedance spectrum, (f) NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4 at a current density of 150 mA·cm -2 The current-time curve when . DETAILED DESCRIPTION

[0027] Preparation Example of Multiphase Composite Material Pretreatment of NF A NF sheet with a size of 2 cm × 3 cm (3.4 mmol) was placed in a 1 M hydrochloric acid solution and ultrasonically cleaned for about 30 minutes to remove the metal oxide layer on the surface. It was then ultrasonically cleaned with acetone for about 30 minutes, rinsed with deionized water and anhydrous ethanol for 8 times in sequence, and finally immersed in anhydrous ethanol and covered with a sealing film for later use.

[0028] Example 1 241.9 mg (1 mmol) sodium molybdate dihydrate (Na2MoO4·2H2O) and 443.8 mg (4 mmol) selenium dioxide (SeO2) were weighed and dissolved in 30 mL deionized water. The mixture was stirred for about 30 minutes to form a uniform, transparent, colorless solution. One piece of treated NF (2 cm×3 cm) and the resulting solution were transferred to a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner and sealed. The reaction was carried out at 180°C for 12 hours. After the reaction, the autoclave was cooled to room temperature naturally, washed with deionized water and anhydrous ethanol three times respectively, and dried in vacuum at 40°C. The obtained product was recorded as NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4.

[0029] Example 2 The composite material was synthesized according to the scheme of Example 1, except that the amount of SeO2 was changed to 1 mmol. The obtained product was recorded as NiMoO4 / Ni3Se2 / NF.

[0030] Example 3 The composite material was synthesized according to the scheme of Example 1, except that the amount of SeO2 was changed to 3 mmol. The obtained product was recorded as NiMoO4 / Mo3Se4 / Ni3Se2 / NF-3.

[0031] Example 4 The composite material was synthesized according to the scheme of Example 1, except that the amount of SeO2 was changed to 5 mmol. The obtained product was recorded as NiMoO4 / Mo3Se4 / Ni3Se2 / NF-5.

[0032] Comparative Example 1 According to the scheme of Example 1, a composite material was synthesized without adding SeO2, and the obtained product was recorded as NiMoO4 / NF.

[0033] Characterization of multiphase composites X-ray diffraction (XRD) characterization Figure 1 XRD patterns of samples NiMoO4 / NF (Comparative Example 1), NiMoO4 / Ni3Se2 / NF (Example 2), NiMoO4 / Mo3Se4 / Ni3Se2 / NF-3 (Example 3), NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4 (Example 1), and NiMoO4 / Mo3Se4 / Ni3Se2 / NF-5 (Example 4) prepared in Examples 1-4 and Comparative Example 1. Figure 1 As can be seen in (A), strong diffraction peaks at 44.5°, 51.8°, and 76.4° can be observed in all five samples, corresponding to Ni 0 Standard card (JCPDS No. 04-0850, ), indicating that NF still exists in all samples. When SeO2 is not added, it can be seen from (a) in (B) that in addition to the diffraction of NF, diffraction at 13.2° is also observed, corresponding to NiMoO4, indicating that the generated product is NiMoO4 / NF. When the amount of SeO2 is 1 mmol (as shown in (b) in (B)), diffraction peaks are observed at 13.2° and 23.5°, corresponding to NiMoO4, and diffraction peaks are also observed at 29.6° and 29.9°, corresponding to Ni3Se2, indicating that a composite material NiMoO4 / Ni3Se2 / NF of two phases of NiMoO4 and Ni3Se2 is formed at this time. When the amount of SeO2 is increased to 3 mmol, 4 mmol and 5 mmol, the products (as shown in (c), (d) and (e) in (B)) have diffraction peaks at 13.2°, 19.9°, 23.5° and 25.4° corresponding to NiMoO4 (JCPDS No. 12-0348, with ), while the peaks at 20.9°, 29.6° and 29.9° are respectively attributed to Ni3Se2 (JCPDS No. 19-0841, At this time, diffraction peaks were also observed at 13.4°, 26.8° and 27.7°, corresponding to Mo3Se4 (JCPDS No. 21-0575, The (001), (002) and (101) crystal planes of the composite material (represented by (001), (002) and (101) indicate that a composite material NiMoO4 / Mo3Se4 / Ni3Se2 / NF containing three phases of NiMoO4, Mo3Se4 and Ni3Se2 was obtained.

[0034] It can be seen that when no SeO2 is added, only NiMoO4 is generated on NF, and the product is NiMoO4 / NF; when the amount of SeO2 added is small (1 mmol), SeO2 and Ni 2+ and Ni 0 (both from NF) react to form Ni3Se2, while MoO4 2- with Ni 2+ The reaction generates NiMoO4, thus obtaining the composite NiMoO4 / Ni3Se2 / NF; when the amount of SeO2 is increased to 3 ~ 5 mmol, in addition to generating Ni3Se2, part of MoO4 2- It is reduced by metal Ni and selenized to form Mo3Se4. In addition, the excess MoO4 2- with Ni 2+The reaction generates NiMoO4, thus obtaining a three-phase composite material NiMoO4 / Mo3Se4 / Ni3Se2 / NF. NF acts as a reducing agent in the above reaction process, reducing +6-valent Mo to +4-valent and reducing +4-valent Se to -2-valent.

[0035] Scanning electron microscopy (SEM) characterization Figure 2 This is a scanning electron microscope (SEM) photograph of the sample. Figure 2 (a1)-(a4) are SEM photos of NiMoO4 / NF, showing that the surface of nickel foam is covered with triangular nanosheets (thickness 10-20 nm). Figure 2 (b1)-(b4) are SEM images of NiMoO4 / Ni3Se2 / NF. The surface of nickel foam is aggregated with microspheres (2-3 μm in diameter) composed of interlaced nanosheets. Figure 2 (c1)-(c4), (d1)-(d4), (e1)-(e4) are SEM photos of NiMoO4 / Mo3Se4 / Ni3Se2 / NF-3, NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4, and NiMoO4 / Mo3Se4 / Ni3Se2 / NF-5, respectively. From these pictures, we can observe two different morphologies on the composite materials, including flower-like structures (microflowers, assembled from sheets with a thickness of 2 microns and a length of 50-70 microns) grown on the corners of the NF skeleton, and irregular smooth nanospheres (about 400-600 nm in size) tightly covered on the NF surface. Compared with NiMoO4 / Mo3Se4 / Ni3Se2 / NF-3 ( Figure 2 c1), NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4 ( Figure 2 The surface of NiMoO4 / Mo3Se4 / Ni3Se2 / NF-5 has more microflowers, which increases the specific surface area of ​​the material, making it more conducive to the full contact between the electrolyte and the electrolytic process, and is conducive to the improvement of electrocatalytic performance. The morphology of NiMoO4 / Mo3Se4 / Ni3Se2 / NF-5 is similar to that of NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4, but its NF skeleton has cracks ( Figure 2 (e1) in the figure) may lead to a decrease in the conductivity of the material and affect the catalytic effect.

[0036] EDS (Energy-dispersive X-ray spectroscopy) test was performed on NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4, such as Figure 3 As shown, Figure 3 The area in (a) is Figure 3(b)-(e) show the presence of four elements Ni, Mo, Se, and O in the material. From the concentrated distribution of O element in (e), it can be inferred that the micro-flower structure corresponds to NiMoO4 phase. According to the concentrated distribution of Se element in the upper left corner in (d), it can be inferred that Ni3Se2 and Mo3Se4 may cover the NF skeleton, and these two phases may form a stable heterostructure.

[0037] X-ray photoelectron spectroscopy (XPS) characterization In order to analyze the valence state and chemical environment of elements in NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4, X-ray photoelectron spectroscopy (XPS) tests were carried out. Before fitting, all peak positions were corrected using the C1s peak (284.8 eV). The results are shown in Figure 4 , proving the existence of Ni, Mo, Se and O elements. Figure 4 (a) is the Ni 2p spectrum. The two peaks at 856.3 and 874.0 eV correspond to Ni 2+ 2p 3 / 2 and 2p 1 / 2 , the peaks at 861.8 and 879.8 eV correspond to the satellite peaks of Ni.

[0038] Figure 4 (b) is the Mo 3d spectrum. The two peaks at 232.6 and 235.7 eV correspond to Mo 6+ 3D 5 / 2 and 3D 3 / 2 , classified as NiMoO4 phase; the two peaks at 228.7 and 231.8 eV correspond to Mo 4+ 3D 5 / 2 and 3D 3 / 2 , classified as Mo3Se4 phase. 4+ The appearance of NF (Ni 0 ) MoO4 2- Mo 6+ Restore to Mo 4+ .

[0039] Figure 4 (c) is the Se 3d spectrum. The two peaks with binding energies of 55.1 and 55.8 eV correspond to Se 2- 3D 5 / 2 and 3D 3 / 2 . This indicates that SeO2 is NF (Ni 0 ) is reduced to Se 2- , and then with NF (Ni 0 )Reduced Mo 4+ Mo3Se4 is obtained by combining. The peak at 59.2 eV is attributed to SeO x, which may correspond to the surface oxidation products of the sample in air.

[0040] Figure 4 (d) is the O 1s spectrum. The two peaks with binding energies of 531.1 and 532.2 eV correspond to oxygen bound to the metal and oxygen in H2O adsorbed on the surface of the material, respectively.

[0041] HER catalytic performance testing of multiphase composites The HER performance of samples NiMoO4 / NF (Comparative Example 1), NiMoO4 / Ni3Se2 / NF (Example 2), NiMoO4 / Mo3Se4 / Ni3Se2 / NF-3 (Example 3), NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4 (Example 1), and NiMoO4 / Mo3Se4 / Ni3Se2 / NF-5 (Example 4) prepared in Examples 1-4 and Comparative Example 1 was tested. The electrochemical test adopts a standard three-electrode system, and the above samples can be directly used as working electrodes (fix the samples with electrode clamps so that the area immersed in the electrolyte is 1cm 2 ), the counter electrode was a platinum electrode, the reference electrode was a Hg / HgO electrode, and the electrolyte was 1 M KOH solution.

[0042] The polarization curve was tested by linear sweep voltammetry (LSV), the scan rate was set to 5 mV / s, and the test results were corrected by 90% iR. Figure 5 As shown in (a) and (b), for NiMoO4 / Mo3Se4 / Ni3Se2 / NF- n (n=3, 4, 5), current density up to 10 mA cm -2 The overpotential required (η 10 ) is 62-80 mV, much lower than NiMoO4 / NF (η 10 = 201 mV) and NiMoO4 / Ni3Se2 / NF (η 10 = 159 mV). And for NiMoO4 / Mo3Se4 / Ni3Se2 / NF- n, With the increase of the amount of selenium source added, the overpotential first decreases and then increases, that is, the HER catalytic activity first increases and then decreases. Among them, NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4 has the highest catalytic activity, η 10 is 62 mV, which is lower than NiMoO4 / Mo3Se4 / Ni3Se2 / NF-3 (η 10 = 80 mV), NiMoO4 / Mo3Se4 / Ni3Se2 / NF-5 (η 10= 78 mV). Therefore, when preparing NiMoO4 / Mo3Se4 / Ni3Se2 / NF, the amount of selenium source is 3 mmol, 4 mmol, 5 mmol, preferably 4 mmol. This is because when the amount of selenium source is 4 mmol, the three phases of NiMoO4, Mo3Se4, and Ni3Se2 in the obtained composite have suitable relative contents and optimal morphology.

[0043] The Tafel slope of the sample can be obtained from the LSV plot, Figure 5 As can be seen in (c), compared with the single-phase material NiMoO4 / NF (Tafel slope is 207 mV·dec -1 ) and the dual-phase composite NiMoO4 / Ni3Se2 / NF (Tafel slope is 183 mV·dec -1 ), the Tafel slope of the three-phase composite is small, and the Tafel slope of NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4 is the smallest, which is only 35 mV·dec -1 , indicating that it has the fastest HER kinetics.

[0044] Electrochemically active surface area (ECSA) is often used to evaluate the effective active area of ​​the working electrode, due to the electrochemical double layer capacitance (C dl ) is proportional to the ECSA, so it can be expressed by C dl Calculate the ECSA of the catalyst. Figure 5 As shown in (d), compared with NiMoO4 / NF and NiMoO4 / Ni3Se2 / NF, the prepared NiMoO4 / Mo3Se4 / Ni3Se2 / NF- n C dl The larger the value, the more obvious it is, indicating that the three-phase composite material has a larger specific surface area and enhanced electrocatalytic activity, especially NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4 has the largest C dl value, i.e. 21.86 mF·cm -2 , indicating that its electrocatalytic active surface area is the largest.

[0045] The Nengquist impedance spectrum of the sample was tested in the frequency range of 0.01 Hz to 100 kHz. The results are as follows: Figure 5 As shown in (e). NiMoO4 / Mo3Se4 / Ni3Se2 / NF- n R of (n = 3, 4, 5) ct The values ​​of R are 3.63 Ω, 2.25 Ω, and 3.52 Ω, respectively, while the R ctThe values ​​are 9.81 Ω and 5.60 Ω respectively. NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4 has the smallest charge transfer impedance, the fastest HER electron transfer rate, and the strongest conductivity. The specific resistance data are shown in Table 1.

[0046] Using chronoamperometry, NiMoO4 / Mo3Se4 / Ni3Se2 / NF-4 was subjected to a current density of 150 mA·cm -2 The HER stability test was carried out under Figure 5 As shown in (f), it can be seen that after 220 hours of continuous electrolysis, the current density did not decay significantly, reflecting its excellent HER electrocatalytic stability.

[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A multiphase composite material, characterized in that: include: Nickel foam, and NiMoO4, Mo3Se4 and Ni3Se2 grown on the nickel foam.

2. The multiphase composite material according to claim 1, characterized in that: The NiMoO4 appears as a flower-like structure assembled from microsheets, and the Mo3Se4 and Ni3Se2 form a heterojunction and appear as a nanoparticle structure.

3. The multiphase composite material according to claim 1 or 2, characterized in that: The composite is obtained by reacting nickel foam as a nickel source with a molybdenum source and a selenium source soluble in water, wherein the molar ratio of the molybdenum source to the selenium source is 1:(3-5), preferably 1:

4.

4. The multiphase composite material according to claim 3, characterized in that: The molybdenum source is sodium molybdate, and the selenium source is selenium dioxide.

5. A method for preparing a multiphase composite material, characterized in that: include: (1) dissolving a molybdenum source and a selenium source in water at a molar ratio of 1:(3-5) to obtain a molybdenum-selenium solution; (2) allowing the molybdenum-selenium solution to undergo a hydrothermal reaction with nickel foam to obtain the multiphase composite material.

6. The preparation method according to claim 5, characterized in that: The molar ratio of the molybdenum source to the selenium source is 1:

4.

7. The preparation method according to claim 6, characterized in that: The molybdenum source is sodium molybdate, and the selenium source is selenium dioxide.

8. The preparation method according to claim 5, characterized in that: The reaction temperature of the hydrothermal reaction is 160-200° C., and the reaction time is 10-14 hours.

9. Use of the multiphase composite material according to any one of claims 1 to 4 as an electrocatalyst for hydrogen evolution reaction.